Throughfall, stemflow and interception loss of old rubber trees. - Yusop, Zulkifli; Cham, Sze Yen; Chong, Jenn Hui (Faculty of Civil Engineering, UTM, 2003)

(untitled)
An interception study of old rubber trees was carried out in Skudai, Johor. Out of 35 rainfall events recorded, only 28 produced measurable throughfall and stemflow. Throughfall and stemflow comprised 87% and 1.1% of the total rainfall, respectively. These resulted in interception loss of 12.1% of the rainfall. Both throughfall and stemflow showed strong linear correlations against daily rainfall with r2 values of 0.99 and 0.84, respectively. The wettest month of November registered the highest interception, both in term of actual value and as the percentage of rainfall. The canopy storage capacity (S), trunk storage capacity (p) and the fraction of rainfall that goes to trunk (p) were 0.11 mm, 0.017 mm and 6.45 mm, respectively.